A Study to Assess Knowledge and Attitude Towards HIV among Students from Pune City - Soumiksha1 , Jomol1 , Anushri1 , Madhura1 , Shefali1 , Sharadha Ramesh2 , Dipak Sethi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: India has the third largest HIV epidemic in the world. The Indian epidemic is characterized bylow levels in the general population and elevated concentrations among high-risk groups. The present studywas planned to determine the awareness of HIV among students from Pune city.Methods: A cross-sectional study was carried out among students from Pune city, India during March, 2020.50 students were approached to participate in the study (males: 32; females: 18). Pretested questionnaire wasdistributed and collected data was analyzed using SPSS version 16.Results: Study participants had high knowledge (86%) and attitude score (87%). There was no significantdifference between males and female participants for attitude and knowledge, except for one questionregarding knowledge about HIV transmission via breastfeeding to child.Conclusions: Present study showed that there are no misconceptions or negative attitudes regarding HIVamong students.